PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL DALAM PERKEMBANGAN TEKNOLOGI DIGITAL DAN ARTIFICIAL INTELLIGENCE DI INDONESIA - Silalahi, Wilma; Satria Adi Pratama (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of digital technology and Artificial Intelligence (AI) has brought significant changes to the process of creating, distributing and utilizing intellectual works in Indonesia. These technological advances encourage increased innovation and the creative economy, but on the other hand, they create new challenges in the protection of Intellectual Property Rights (IPR), especially regarding ownership of Artificial Intelligence-based works, digital copyright infringement, and the distribution of content without permission via online platforms. This research aims to analyze the form of IPR legal protection in facing the development of digital technology and Artificial Intelligence in Indonesia and identify the need for updating national legal regulations. The research method used is normative legal research with statutory, conceptual and comparative analysis approaches. The research results show that the IPR legal framework in Indonesia has provided basic protection through the Copyright, Patent and Trademark Law, but has not optimally accommodated the development of Artificial Intelligence technology. The main problems lie in the unclear legal subject of creators of AI works, weak monitoring of digital violations, and low IPR literacy in society. Therefore, it is necessary to reformulate legal policies that are adaptive to technology, strengthen digital law enforcement, and collaborate between the government, technology industry and society to create an effective and sustainable IPR protection system in the era of digital transformation.